1998
DOI: 10.1021/jp982456x
|View full text |Cite
|
Sign up to set email alerts
|

Indole−H2O in the Gas Phase. Structures, Barriers to Internal Motion, and S1 ← S0 Transition Moment Orientation. Solvent Reorganization in the Electronically Excited State

Abstract: Rotationally resolved S 1 r S 0 fluorescence excitation experiments have been performed on a solute-solvent complex of indole and water in a molecular beam. The results show that the complex whose S 1 r S 0 origin is shifted by 132 cm -1 below the bare molecule origin is a 1:1 complex, with the water molecule linked to the indole frame via a quasi-linear N-H‚‚‚OH 2 σ hydrogen bond. The results also show that both the position and the orientation of the attached water molecule change when the photon is absorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 25 publications
11
100
2
Order By: Relevance
“…In the np à excited state, the hydrated structure was revealed to be completely modified. Such changes in the hydrated structures in the np à state are in accordancewith the established fact that hydrogen bonds are largelydestabilized under np à excitations [43,[156][157][158]. The amino group of the enol tautomer of cytosine is found to be more pyramidal than the keto-N1H tautomer, while it shows a lower degree of pyramidization than the keto-N3H tautomer in the ground state.…”
Section: Excited-state Geometries Of Nucleic Acid Basessupporting
confidence: 80%
See 1 more Smart Citation
“…In the np à excited state, the hydrated structure was revealed to be completely modified. Such changes in the hydrated structures in the np à state are in accordancewith the established fact that hydrogen bonds are largelydestabilized under np à excitations [43,[156][157][158]. The amino group of the enol tautomer of cytosine is found to be more pyramidal than the keto-N1H tautomer, while it shows a lower degree of pyramidization than the keto-N3H tautomer in the ground state.…”
Section: Excited-state Geometries Of Nucleic Acid Basessupporting
confidence: 80%
“…The investigation of polyhydration of adenine, uracil, thymine and cytosine with 11-16 water molecules in the ground state shows significant geometrical deformation of bases [40][41][42]. Korter et al [43] have performed an experimental investigation on the interaction of a water molecule with the N-H site of indole, which could be considered as a simplified model of a DNA base, in the ground and the lowest singlet excited state, and found that, consequent to electronic excitation, the position and orientation of the water molecule were changed with respect to the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case, for example, of the indole±water complex. [1,2] Aliphatic ethers are not chromophores, therefore the use of LIF is not suitable to study their complexes with water. This is probably the reason why only pure rotational spectra has been reported for just a few of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on two water-containing systems here, pDFBW [61] and IW [51]. Figure 13 shows the high resolution electronic spectrum of the pDFBW complex.…”
Section: A5 Water Complexesmentioning
confidence: 99%